Manufacturing Engineering and Materials Handling, Parts a and B 2005
DOI: 10.1115/imece2005-81060
|View full text |Cite
|
Sign up to set email alerts
|

The Reduction of Deformation Energy and Increase in Workability of Metals Through an Applied Electric Current

Abstract: Many manufacturing processes (e.g., forging, rolling, extrusion, and sheet metal) rely on the application of heat to reduce the forces associated with fabricating parts. However, due to the negative implications associated with hot working, another more efficient means of applying energy is desired. This paper investigates the changes in the material properties of various metals (aluminum, copper, iron, and titanium based alloys) in response to electricity flow. Theory involving electromigration, and, more spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In recent years, research on EPE has become increasingly popular [3][4][5][6] since this effect has found applications in various industries. Due to the skin effect [7], a non-thermal reduction in flow stress can be observed in relatively thin workpieces in such manufacturing processes as drawing [8,9], rolling [10,11], stamping [12], forging [13,14], cutting [15], and forming [5,6,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research on EPE has become increasingly popular [3][4][5][6] since this effect has found applications in various industries. Due to the skin effect [7], a non-thermal reduction in flow stress can be observed in relatively thin workpieces in such manufacturing processes as drawing [8,9], rolling [10,11], stamping [12], forging [13,14], cutting [15], and forming [5,6,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%